Beispiel Nr: 24
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ -5\frac{1}{16}x^3+10\frac{1}{8}x^2 =0\\ \\ \textbf{Rechnung:} \\ x^2(-5\frac{1}{16}x+10\frac{1}{8})=0 \Rightarrow x=0 \quad \vee \quad-5\frac{1}{16}x+10\frac{1}{8}=0\\ -5\frac{1}{16} x+10\frac{1}{8} =0 \qquad /-10\frac{1}{8} \\ -5\frac{1}{16} x= -10\frac{1}{8} \qquad /:\left(-5\frac{1}{16}\right) \\ x=\displaystyle\frac{-10\frac{1}{8}}{-5\frac{1}{16}}\\ x=2 \\ \underline{x_1=0; \quad2\text{-fache Nullstelle}} \\\underline{x_2=2; \quad1\text{-fache Nullstelle}} \\$